Analysis of the implementation of patient safety management at the PKU Muhammadiyah Pekajangan Islamic Hospital - Irnawati; Benny Arief Sulistyanto (Proceedings Series on Health & Medical Sciences, 2020)
The Hospital applies patient safety management through seven steps toward hospital patient safety. Muhammadiyah Pekajangan Islamic Hospital already has special management that handles patient safety. The patient safety management has gone through the planning stage to evaluation. In its development, until now, there has not been an analysis of the application of patient safety management. Analysis of the application of patient safety management is important to determine whether the application of patient safety management is already running according to the established Ministry of Health standards. This study aims to analyze the application of patient safety management at the PKU Muhammadiyah Pekajangan Islamic Hospital. This study was used as a qualitative research design. The subjects in this study who conducted in-depth interviews were the PKU Muhammadiyah Pekajangan Islamic Hospital patient safety team, which consists of the head of the KPRS, who had the authority to carried outpatient safety activities, members of nursing, and members of medical support. The results showed that the application of patient safety management is performing admirably. Includes seven-step implementation of patient safety management has been actualized. The process application of patient safety management shows that the indicators were in line with the standards. It is recommended for policymakers at the PKU Muhammadiyah Pekajangan Islamic Hospital to increase efforts to implement patient safety by facilitating training for the patient safety team regarding patient safety.